CMOS Integrated Tungsten Oxide Nanowire Networks for ppb-level H2S Sensing. (2016) - Krainer, J.; Deluca, M.; Lackner, E.; Wimmer-Teubenbacher, R.; Sosada, F.; Gspan, C.; Rohracher, K.; Wachmann, E.; Koeck, A.
Abstract: Tungsten oxide is an intensively studied semiconductor with the relevant application as H2 S gas sensor. In this work we report on H2 S gas sensor devices based on tungsten oxide nanowire networks, which are integrated on a CMOS fabricated microhotplate chip. Tungsten oxide gas sensors were prepared by the deposition of nanowire networks onto interdigitated electrodes on CMOS. The material properties of the tungsten oxide nanowires were investigated by TEM and Raman spectroscopy, confirming their non-stoichiometric state. Utilising WO3-x nanowire networks as gas sensing material we obtained extraordinary sensitivity to H2 S: concentrations down to 10 ppb have been detected, even in the presence of 50% relative humidity.